2012
DOI: 10.1097/pec.0b013e31823f2315
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Opinions About Suicide Screening in a Pediatric Emergency Department

Abstract: Objective Understanding how children react to suicide screening in an emergency department (ED) can inform implementation strategies. This qualitative study describes pediatric patients’ opinions regarding suicide screening in that setting. Methods As part of a multisite instrument validation study, patients 10 to 21 years presenting with both psychiatric and nonpsychiatric complaints to an urban, tertiary care pediatric ED were recruited for suicide screening. Interviews with subjects included the question,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…45 In another emergency department study, most youth said they were comfortable with being asked by a nurse about suicidality. 63 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 In another emergency department study, most youth said they were comfortable with being asked by a nurse about suicidality. 63 …”
Section: Resultsmentioning
confidence: 99%
“…Eight of the studies reviewed excluded families that did not speak English; 41, 50, 59, 63, 64, 6769 many others (n=20) did not state the language in which screening was administered. Only 3 studies reported that parents or youth were able to ask for assistance when completing screens, 34, 42, 58 and one computer-administered screen had an option that allowed the respondent to listen to the questions as they were presented.…”
Section: Resultsmentioning
confidence: 99%
“…(15) Two raters, a doctoral level clinical psychologist and a bachelor’s level research assistant, coded the data using the same themes drawn from a previous analysis. (14) Inter-rater agreement for these themes ranged from 88%–100%. Additionally, the raters used open coding procedures for other themes that emerged from the data.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, Ballard and colleagues published a qualitative investigation of patient opinions about suicide risk screening. (14) The five most salient themes that emerged from open coding responses of patients who supported suicide risk screening were: 1) identification of at-risk youth; 2) a desire for clinicians to know and understand their situation; 3) connection of youth with mental health help and resources; 4) prevention of suicidal behavior; and 5) lack of other individuals to speak with about these issues. These responses emphasized the importance of suicide risk screening, highlighting its potential to link patients to mental health treatment.…”
mentioning
confidence: 99%
“…Studies have shown that pediatric patients in the emergency department favor suicide risk screening; 18, 19 however, it is not known how adult patients hospitalized for medical reasons will react to questions about suicide, particularly in the context of medical treatment. The objective of this paper is to describe patients’ opinions and reactions to universal screening for suicide risk in an inpatient medical hospital setting using qualitative analysis.…”
Section: Introductionmentioning
confidence: 99%